The economic assessment of soil nutrient depletion: Analytical issues for framework development - Drechsel, Pay; Gyiele, L.A. (IBSRAM, 1999)
The two major objectives of this publication are (i) to provide an overview about the assessment of nutrient depletion and the major processes of nutrient depletion, and (ii) to provide an overview on different economic valuation approaches for nutrient depletion, including carbon depletion, and thus add to their discussion.